SWELLMAP 2, a phyB-Interacting Splicing Factor, Negatively Regulates Seedling Photomorphogenesis in Arabidopsis - Yan, Tingting; Heng, Yueqin; Wang, Wenwei; Li, Jian; Deng, Xing Wang (Frontiers in Plant Science, 2022)
Light-triggered transcriptome reprogramming is critical for promoting photomorphogenesis in Arabidopsis seedlings. Nonetheless, recent studies have shed light on the importance of alternative pre-mRNA splicing in photomorphogenesis. The splicing factors SFPS and RRC1 are involved in the phytochrome B (phyB) signaling pathway and promote photomorphogenesis by controlling pre-mRNA splicing of light- and clock-related genes. However, splicing factors that serve as repressors in phyB signaling pathway remain unreported. Here, we report that the splicing factor SWELLMAP 2 (SMP2) suppresses photomorphogenesis in the light. SMP2 physically interacts with phyB and colocalizes with phyB in photobodies after light exposure. Genetic analyses show that SMP2 antagonizes phyB signaling to promote hypocotyl elongation in the light. The homologs of SMP2 in yeast and human belong to second-step splicing factors required for proper selection of the 3' splice site (3'SS) of an intron. Notably, SMP2 reduces the abundance of the functional REVEILLE 8 a (RVE8a) form, probably by determining the 3'SS, and thereby inhibits RVE8-mediated transcriptional activation of genes in the evening phase. Finally, SMP2-mediated reduction of functional RVE8 isoform promotes PIF4 expression to fine-tune hypocotyl elongation in the light. Taken together, our data unveil a phyB-interacting splicing factor that negatively regulates photomorphogenesis, providing additional information for further mechanistic investigations regarding phyB-controlled AS of light- and clock-related genes.